AN INTER-COMPARISON OF PASSIVE DOSEMETERS FOR TERRESTRIAL GAMMA RADIATION MEASUREMENTS. Issue 16 (15th July 2022) - Ding, Yanqiu; Wang, Kaiyi; Gao, Pin; Hu, Aiying; Guo, Wen; Han, Yanqing
Abstract: To evaluate the measurement method of passive dosemeters for terrestrial gamma radiation measurements. An inter-comparison of passive dosemeters for terrestrial gamma radiation measurements was organized alternately by the Japan Chemical Analysis Center, National Institute for Radiological Protection of Chinese Center for Disease Control and Prevention and Radiation Monitoring Technical Center of Ministry of Environmental Protection every 2 years. The procedures and exposure conditions of the field-exposure and reference irradiation test were provided by the organizer. During 2019–2020, the En values of Field-1 and Field-2 in three laboratories were lower than 1.0 and assigned 'acceptable' according to inter-comparison criteria. After the correction of the fading effect of dosemeter material, the En values of reference irradiation test (0.301 mGy, 1.000 mGy) in three laboratories were lower than 1.0 and assigned 'acceptable'.